PENINGKATAN PERFORMANCE SYSTEM PADA DEPARTEMEN PACKAGING DENGAN SIMULASI PROSES DAN REDESIGN WORKSTATION (Studi Kasus : CV. Segar Buah Hutama, Batu) - Nuzullis Lailatul Kamaliyah; Sugiono Sugiono; Widya Wijayanti (Journal of Engineering and Management in Industrial System, 2015)
Abstract In running the process, the repetitive activity in the production process of the extract of Dewata fruit could cause pain and fatigue on the worker's body. It was because there was a facility that did not meet the rules of workplace ergonomics. Continuous evaluation was needed to know the solution of the problem of musculoskeletal complaint so that it can improve ergonomic working facilities. In making simulation scenario is expected to describe the condition of the actual company so that the improvement proposal can resolve the real issue.The methods that were used in this study include: Biomechanics Assessment (REBA and QEC), anthropometric Design and Simulation Arena. Assessment scores REBA (Rapid Entire Body Assessment) was obtained from the angle of motion depiction of the image carrier (photo) whereas the assessment scores QEC (Quick Exposure Check) was obtained from filling the questionnaire between the observer and the operator. From the research result on the dimension repair facility cooling pond work on workstation 2 (cooling), tables and chairs on the workstation 3 (formation of cardboard box), and the table packaging on the workstation 4 (packaging). In the proposal of improved simulation, it is given resource addition as many as one person on cooling 2 to improve production efficiency from 42.3 % to 100 % so that it is necessary to increase the wage of Rp 1,500,000.00 / month.